Manajemen Keuangan dan Pengembangan Pelatihan Pendidik dan Tenaga Kependidikan AUD - Rahayu, Kurnia; Lovita, Resi; Cletus Lamatokan, Sisca; Darajat , Iik Dzakiah (Pusat Riset dan Inovasi Nasional, 2025)
The quality of early childhood education is fundamentally dependent on the competence of educators and educational staff, which necessitates continuous professional development programs. However, the implementation of sustainable training initiatives requires a structured and accountable financial management system to optimize resource allocation effectively. This study aims to analyze financial management practices in organizing training programs for early childhood educators and staff, identify factors influencing budgeting effectiveness for professional development, and formulate an integrative financial management model to support training program sustainability. Employing a qualitative approach with library research methodology, this study systematically collected and analyzed academic literature including accredited journals, textbooks, research reports, and policy documents published between 2020-2025. Content analysis was conducted through identification and selection of relevant sources, extraction of key information, thematic categorization, synthesis of findings, and in-depth interpretation of conceptual relationships between financial management and professional development. Findings reveal that institutions with transparent and accountable financial management systems demonstrate superior capacity in allocating budgets for regular training activities, positively impacting learning quality. Major challenges include limited understanding of School Revenue and Expenditure Budget planning, insufficient budgeting transparency, and weak financial accountability systems. Training programs on financial reporting and bookkeeping effectively enhance managerial competencies, while flexible online professional development workshops generate significant transformation in pedagogical creativity and practice quality. Strategic integration between structured financial management and continuous capacity building programs constitutes an essential prerequisite for holistic quality improvement in early childhood education. The study recommends that institutions allocate adequate and consistent budget proportions for educator training, implement technology-based bookkeeping systems, and develop innovative financing strategies through revenue diversification and entrepreneurial programs to overcome budget limitations.